Research on the personalised QoE evaluation method for HTTP mobile streaming. (2016) - Zhou, Wen'an; Huang, Yajun; Yu, Shipeng; You, Liyan; Du, Yu
The demand of HTTP mobile streaming services over mobile networks has been increasing drastically in recent years. QoE evaluation and optimisation technologies play a crucial role for the operators in the competitive market. However, due to the complexity and diversity of user behaviour, only the factors in the network and application layers are considered in most of the current QoE evaluation methods. In this paper, we focus on personalised QoE evaluation method based on user behaviours for HTTP mobile streaming services. We propose a QoE evaluation method based on feedbacks sent from the users on purpose. Then we propose a method based on users' unconscious feedbacks, for example, the number of users operations during their viewing session. The evaluated QoE by proposed methods is much closer to the users' actual feelings than traditional methods, which verifies the optimality of our proposed scheme.